A high specific energy lithium manganese iron phosphate positive electrode material and preparation method thereof
By using modified xanthan gum and carbon nanotubes in the lithium manganese phosphate positive electrode material to perform hydrothermal reaction and high-temperature sintering after ball milling, the problems of manganese dissolution and low conductivity are solved, and the electrochemistry of the material is significantly improved Performance and cycle stability.
Patent Information
- Application Number
- CN202411738414.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In actual use, the lithium manganese iron phosphate positive electrode material is prone to manganese dissolution, resulting in a decrease in battery capacity and cycle life, and the low conductivity of the olivine structure leads to poor electrochemical performance.
The thickness of the carbon cladding is prepared by adding modified xanthan gum into lithium manganese iron phosphate and carbon nanotubes to form an organic-inorganic carbon source, undergoing hydrothermal reaction and ball milling, and undergoing high-temperature sintering under the protection of inert gas to prepare the thickness of the carbon cladding layer by performing hydrothermal reaction and ball milling. Uniform lithium manganese iron phosphate positive electrode material.
It significantly improves the conductivity and battery performance of lithium manganese iron phosphate material, improves cycle stability and electrochemical performance, extends the cycle life of the battery, reduces manganese dissolution, and improves the overall performance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a high-energy lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] In recent years, lithium-ion batteries have made great achievements in the application of consumer electronics, energy storage power stations and electric vehicles. As one of the key materials in the lithium-ion battery system, cathode materials have received extensive attention. At present, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide and nickel cobalt manganese oxide ternary cathode materials are the most commercialized materials.
[0003] At present, lithium manganese iron phosphate (LiFe x Mn 1-x Lithium iron phosphate (LiFePO4) is considered a promising alternative, mainly due to the solid solution that combines the advantages of the relatively high electronic conductivity of LiFePO4 and the relatively high voltage of LiMnPO4. By introducing manganese into lithium iron phosphate, while maintaining the advantages of the olivine structure, lithium manganese iron phosphate batteries have higher energy density, better stability, longer cycle life and high safety compared to lithium iron phosphate batteries, and their performance at low temperatures is also better. However, in actual use, manganese is easily dissolved from the positive electrode of lithium manganese iron phosphate, resulting in lattice distortion, resulting in reduced battery capacity and cycle life. In addition, the problem of poor electrochemical performance caused by the low conductivity of lithium iron phosphate and lithium manganese phosphate with olivine structure also exists.
[0004] Therefore, further optimizing the electrochemical performance of lithium manganese iron phosphate positive electrode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In order to improve the electrochemical performance of lithium iron manganese phosphate positive electrode materials, the present invention provides a high specific energy lithium iron manganese phosphate positive electrode material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing a high specific energy lithium manganese iron phosphate positive electrode material comprises the following steps:
[0008] Step 1, adding carbon nanotubes into deionized water, ultrasonically dispersing, adding modified xanthan gum, ammonia water and hydrazine hydrate, stirring for 5-10 minutes, heating to 55-60°C, continuing stirring for 4-4.5 hours, filtering, washing, and drying to obtain a carbon source;
[0009] Step 2, adding the lithium hydroxide solution to the phosphoric acid solution, stirring and dispersing, adjusting the pH value, adding the manganese sulfate solution and the ferrous sulfate solution, and then transferring to a hydrothermal reactor for a hydrothermal synthesis reaction to obtain a hydrothermal reaction product;
[0010] Step 3, centrifuging the hydrothermal reaction product obtained in step 2, separating the solid from the liquid, washing the solid product with anhydrous ethanol and deionized water, drying, and mixing the dried product with the carbon source obtained in step 1 to obtain a mixture;
[0011] Step 4, ball milling the mixture obtained in step 3 to obtain a powder;
[0012] Step 5, calcining the powder obtained in step 4 under the protection of inert gas, and naturally cooling to room temperature to obtain a high specific energy lithium manganese iron phosphate positive electrode material;
[0013] Wherein, the modified xanthan gum described in step 1 is prepared by the following steps:
[0014] Add xanthan gum to sodium hydroxide solution, heat and stir to dissolve it, add 1,4-butanesulfonic acid lactone dropwise, stir and react at 70-75°C for 4-4.5 hours, cool to room temperature, adjust the pH value to 9-9.2, then add methanol until no more white precipitate is precipitated, let stand for 12-14 hours, filter and wash, and vacuum dry to constant weight to obtain modified xanthan gum.
[0015] Furthermore, the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3: (1-x): x: 1, wherein 0.1≤x≤0.4.
[0016] Furthermore, in step 1, the usage ratio of carbon nanotubes, deionized water, modified xanthan gum, ammonia water and hydrazine hydrate is 0.010-0.015 g: 20 mL: 0.32-0.36 g: 0.30 mL: 0.02 mL.
[0017] Furthermore, the usage ratio of xanthan gum, sodium hydroxide solution and 1,4-butanesulfonate is 5.0-5.5 g:10 mL:3.0-3.2 mL.
[0018] Furthermore, in step 2, the pH value is adjusted to 9-11.
[0019] Furthermore, in step 2, the hydrothermal synthesis reaction temperature is 180-220° C., and the reaction time is 12-22 h.
[0020] Furthermore, the amount of carbon source added in step 3 is 10%-18% of the mass of the dry product.
[0021] Furthermore, in step 4, the ball milling speed is 350-400 r / min, and the ball milling time is 3-4 h.
[0022] Furthermore, in step 5, the calcination temperature is 550-600° C., the calcination time is 4-8 h, and the heating rate is 3-5° C. / min.
[0023] A high specific energy lithium manganese iron phosphate positive electrode material is prepared by the above steps.
[0024] Beneficial effects of the present invention:
[0025] 1) In the present invention, the raw material lithium hydroxide solution is dissolved in a phosphoric acid solution for hydrothermal reaction to obtain a lithium iron manganese phosphate precursor, which is then mixed with a carbon source, and finally ball milled and sintered at high temperature to obtain a lithium iron manganese phosphate positive electrode material. The carbon coating layer of the organic-inorganic carbon source coated lithium iron manganese phosphate positive electrode material prepared by the present invention has a uniform thickness, excellent electrochemical properties, and stable cycle performance. In addition, the preparation method of the present invention has a simple process flow, low requirements on equipment, and is suitable for large-scale industrial production.
[0026] 2) The carbon source in the present invention uses modified xanthan gum and carbon nanotubes to form an organic-inorganic carbon source, which is then evenly coated on the surface of the lithium iron manganese phosphate positive electrode material to form a stable carbon layer structure. Compared with the use of a single organic or inorganic carbon source, the use of a composite carbon source can more comprehensively improve the electrochemical properties of the lithium iron manganese phosphate material, and significantly improve the conductivity and battery performance of the lithium iron manganese phosphate material by forming a more uniform coating layer and a better conductive network. The addition of a carbon source during the preparation process, on the one hand, controls the particle size of the lithium iron manganese phosphate, inhibits the secondary agglomeration of the lithium iron manganese phosphate crystals, and promotes the uniform particle size of the prepared lithium iron manganese phosphate, thereby increasing the compaction density of the lithium iron phosphate material. On the other hand, through the synergistic effect of xanthan gum and carbon nanotubes, the electrochemical properties of the lithium iron manganese phosphate positive electrode material can be significantly improved, the electronic conductivity between particles can be improved, and the polarization of the positive electrode material during the charge and discharge process of the battery can be reduced. At the same time, the layered structure of the carbon layer can provide an electron tunnel for the lithium iron manganese phosphate, increase the lithium ion deintercalation rate, and ensure the balance of charge. In addition, the modified xanthan gum has a large number of anions (sulfonate ions) on the molecule, which can capture dissolved manganese in advance, thereby inhibiting the dissolution of manganese.
[0027] 3) Xanthan gum is a microbial extracellular polysaccharide and a green natural carbon source. In the present invention, 1,4-butanesulfonic acid lactone is used to react with xanthan gum to undergo sulfonation reaction, thereby improving the water solubility of xanthan gum and obtaining a polyanionic oligosaccharide. The anions (sulfonate ions) on the modified xanthan gum molecules have a strong binding force with transition metal ions, so the dissolved manganese can be captured in advance to avoid the dissolution of manganese, thereby stabilizing the structure of the lithium iron manganese phosphate positive electrode material and further improving the electrochemical performance of the lithium iron manganese phosphate positive electrode material.
[0028] 4) The tap density of the lithium manganese iron phosphate positive electrode material prepared by the present invention is higher than 0.97g / cm -3 At a discharge rate of 0.1C, the first discharge specific capacity can reach up to 165.5mAh / g, and at a discharge rate of 1C, the first discharge specific capacity can reach up to 155.6mAh / g. After 100 cycles, it can still maintain excellent discharge specific capacity. It has excellent electrochemical properties and cycle performance, further broadening the application range of lithium manganese iron phosphate positive electrode materials. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a modified xanthan gum, which is prepared by the following steps:
[0032] Add 5.05 g of xanthan gum to 10 mL of sodium hydroxide solution (30%), heat and stir to dissolve it, slowly add 3.0 mL of 1,4-butanesulfone, raise the temperature to 70 ° C after the addition is complete, continue stirring to react for 4 hours, cool to room temperature, adjust the pH value to 9, then add methanol until no more white precipitate is precipitated, let stand for 12 hours, filter, dissolve with deionized water after filtration, wash with anhydrous ethanol 3 times, continue to filter, place the solid product in a vacuum oven at 50 ° C to constant weight to obtain modified xanthan gum.
[0033] Example 2
[0034] This embodiment provides a modified xanthan gum, which is prepared by the following steps:
[0035] Add 5.45 g of xanthan gum to 10 mL of sodium hydroxide solution (30%), heat and stir to dissolve it, slowly add 3.18 mL of 1,4-butanesulfone, raise the temperature to 70 ° C after the addition is complete, continue stirring to react for 4 hours, cool to room temperature, adjust the pH value to 9, then add methanol until no more white precipitate is precipitated, let stand for 12 hours, filter, dissolve with deionized water after filtration, wash with anhydrous ethanol 3 times, continue to filter, place the solid product in a vacuum oven at 50 ° C to constant weight to obtain modified xanthan gum.
[0036] Example 3
[0037] This embodiment provides a method for preparing a high specific energy lithium manganese iron phosphate positive electrode material, and the preparation steps are as follows:
[0038] Step 1, add 0.013g of carbon nanotubes to 20mL of deionized water, ultrasonically disperse for 1h, add 0.32g of modified xanthan gum in Example 1, 0.30mL of ammonia water (25%) and 0.02mL of hydrazine hydrate (80%), stir for 5min, heat to 55°C, continue stirring for 4h, filter, wash and dry to obtain a carbon source;
[0039] Step 2, adding lithium hydroxide solution to phosphoric acid solution, stirring and dispersing, adjusting the pH value to 9, adding manganese sulfate solution and ferrous sulfate solution, and then transferring to a hydrothermal reactor for hydrothermal synthesis reaction, the hydrothermal synthesis reaction temperature is 180° C., the reaction time is 22 hours, and a hydrothermal reaction product is obtained, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.85:0.15:1;
[0040] Step 3, centrifuging and solid-liquid separation of the hydrothermal reaction product obtained in step 2, washing the solid product with anhydrous ethanol and deionized water, drying, and mixing the dry product with the carbon source obtained in step 1, wherein the amount of the carbon source added is 12% of the mass of the dry product to obtain a mixture;
[0041] Step 4, ball milling the mixture obtained in step 3, the ball milling speed is 350r / min, the ball milling time is 4h, to obtain a powder;
[0042] Step 5: calcining the powder obtained in step 4 under inert gas protection at a calcination temperature of 550°C, a calcination time of 7h, a heating rate of 3°C / min, and naturally cooling to room temperature to obtain a high specific energy lithium manganese iron phosphate positive electrode material.
[0043] The high specific energy lithium manganese iron phosphate positive electrode material is prepared through the above steps.
[0044] Example 4
[0045] The only difference from Example 3 is that:
[0046] The modified xanthan gum in Example 1 was replaced by the modified xanthan gum in Example 2.
[0047] Example 5
[0048] The only difference from Example 3 is that:
[0049] 0.32 g of the modified xanthan gum in Example 1 was replaced with 0.34 g of the modified xanthan gum in Example 1.
[0050] Example 6
[0051] The only difference from Example 3 is that:
[0052] 0.32 g of the modified xanthan gum in Example 1 was replaced with 0.36 g of the modified xanthan gum in Example 1.
[0053] Example 7
[0054] The only difference from Example 3 is that:
[0055] Step 2: Add lithium hydroxide solution to phosphoric acid solution, stir and disperse, adjust the pH value to 11, add manganese sulfate solution and ferrous sulfate solution, and then transfer to a hydrothermal reactor for hydrothermal synthesis reaction. The hydrothermal synthesis reaction temperature is 210° C. and the reaction time is 18 hours to obtain a hydrothermal reaction product, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.85:0.15:1.
[0056] Example 8
[0057] The only difference from Example 3 is that:
[0058] Step 2: Add lithium hydroxide solution to phosphoric acid solution, stir and disperse, adjust the pH value to 9, add manganese sulfate solution and ferrous sulfate solution, and then transfer to a hydrothermal reactor for hydrothermal synthesis reaction. The hydrothermal synthesis reaction temperature is 180° C. and the reaction time is 22 hours to obtain a hydrothermal reaction product, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.75:0.25:1.
[0059] Example 9
[0060] The only difference from Example 3 is that:
[0061] Step 2: Add lithium hydroxide solution to phosphoric acid solution, stir and disperse, adjust the pH value to 9, add manganese sulfate solution and ferrous sulfate solution, and then transfer to a hydrothermal reactor for hydrothermal synthesis reaction. The hydrothermal synthesis reaction temperature is 180° C. and the reaction time is 22 hours to obtain a hydrothermal reaction product, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.65:0.35:1.
[0062] Example 10
[0063] The only difference from Example 3 is that:
[0064] Step 3: centrifuge the hydrothermal reaction product obtained in step 2, separate the solid and liquid, wash the solid product with anhydrous ethanol and deionized water, dry it, mix the dry product with the carbon source obtained in step 1, and add the carbon source in an amount of 17% of the mass of the dry product to obtain a mixture.
[0065] Embodiment 11
[0066] The only difference from Example 3 is that:
[0067] Step 4: ball mill the mixture obtained in step 3 at a ball milling speed of 390 r / min for 3.5 h to obtain a powder.
[0068] Example 12
[0069] The only difference from Example 3 is that:
[0070] Step 5: calcine the powder obtained in step 4 under the protection of inert gas at a calcination temperature of 600°C, a calcination time of 7h, a heating rate of 3°C / min, and naturally cool to room temperature to obtain a high specific energy lithium manganese iron phosphate positive electrode material.
[0071] Example 13
[0072] The only difference from Example 3 is that:
[0073] Step 5: calcining the powder obtained in step 4 under inert gas protection at a calcination temperature of 580° C., a calcination time of 5 h, a heating rate of 4° C. / min, and naturally cooling to room temperature to obtain a high specific energy lithium manganese iron phosphate positive electrode material.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing a high specific energy lithium manganese iron phosphate positive electrode material, and the preparation steps are as follows:
[0076] Step 1, adding lithium hydroxide solution to phosphoric acid solution, stirring and dispersing, adjusting the pH value to 9, adding manganese sulfate solution and ferrous sulfate solution, and then transferring to a hydrothermal reactor for hydrothermal synthesis reaction, the hydrothermal synthesis reaction temperature is 180° C., the reaction time is 22 hours, and a hydrothermal reaction product is obtained, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.85:0.15:1;
[0077] Step 2, centrifuging the hydrothermal reaction product obtained in step 1, separating the solid from the liquid, washing the solid product with anhydrous ethanol and deionized water, and drying to obtain a dry product;
[0078] Step 3, ball milling the dried product obtained in step 2 at a ball milling speed of 350 r / min for 4 h to obtain a powder;
[0079] Step 4: calcine the powder obtained in step 3 under the protection of inert gas at a calcination temperature of 550° C., a calcination time of 7 h, a heating rate of 3° C. / min, and naturally cool to room temperature to obtain a high-energy lithium manganese iron phosphate positive electrode material.
[0080] The high specific energy lithium manganese iron phosphate positive electrode material is prepared through the above steps.
[0081] Comparative Example 2
[0082] This comparative example provides a method for preparing a high specific energy lithium manganese iron phosphate positive electrode material, and the preparation steps are as follows:
[0083] Step 1, adding lithium hydroxide solution to phosphoric acid solution, stirring and dispersing, adjusting the pH value to 9, adding manganese sulfate solution and ferrous sulfate solution, and then transferring it to a hydrothermal reactor for hydrothermal synthesis reaction, the hydrothermal synthesis reaction temperature is 180° C., the reaction time is 22 hours, and a hydrothermal reaction product is obtained, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.85:0.15:1;
[0084] Step 2, centrifuging the hydrothermal reaction product obtained in step 1, separating the solid from the liquid, washing the solid product with anhydrous ethanol and deionized water, drying, mixing the dry product with carbon nanotubes, wherein the amount of carbon source added is 12% of the mass of the dry product, to obtain a mixture;
[0085] Step 3, ball milling the mixture obtained in step 2 at a ball milling speed of 350 r / min for 4 h to obtain a powder;
[0086] Step 4: calcine the powder obtained in step 3 under the protection of inert gas at a calcination temperature of 550° C., a calcination time of 7 h, a heating rate of 3° C. / min, and naturally cool to room temperature to obtain a high-energy lithium manganese iron phosphate positive electrode material.
[0087] The high specific energy lithium manganese iron phosphate positive electrode material is prepared through the above steps.
[0088] Comparative Example 3
[0089] The only difference from Comparative Example 2 is that:
[0090] In step 2, the dried product is mixed with xanthan gum.
[0091] Comparative Example 4
[0092] The only difference from Example 3 is that:
[0093] 0.32 g of the modified xanthan gum in Example 1 was replaced with 0.28 g of the modified xanthan gum in Example 1.
[0094] Comparative Example 5
[0095] The only difference from Example 3 is that:
[0096] 0.32 g of the modified xanthan gum in Example 1 was replaced with 0.40 g of the modified xanthan gum in Example 1.
[0097] Comparative Example 6
[0098] The only difference from Example 3 is that:
[0099] Step 2: Add lithium hydroxide solution to phosphoric acid solution, stir and disperse, adjust the pH value to 7.5, add manganese sulfate solution and ferrous sulfate solution, and then transfer it to a hydrothermal reactor for hydrothermal synthesis reaction. The hydrothermal synthesis reaction temperature is 180° C. and the reaction time is 22 hours to obtain a hydrothermal reaction product, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.85:0.15:1.
[0100] Comparative Example 7
[0101] The only difference from Example 3 is that:
[0102] Step 2: Add lithium hydroxide solution to phosphoric acid solution, stir and disperse, adjust the pH value to 9, add manganese sulfate solution and ferrous sulfate solution, and then transfer it to a hydrothermal reactor for hydrothermal synthesis reaction. The hydrothermal synthesis reaction temperature is 160° C. and the reaction time is 22 hours to obtain a hydrothermal reaction product, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3:0.85:0.15:1.
[0103] Comparative Example 8
[0104] The only difference from Example 3 is that:
[0105] Step 2: Add lithium hydroxide solution to phosphoric acid solution, stir and disperse, adjust the pH value to 9, add manganese sulfate solution and ferrous sulfate solution, and then transfer it to a hydrothermal reactor for hydrothermal synthesis reaction. The hydrothermal synthesis reaction temperature is 180° C. and the reaction time is 22 hours to obtain a hydrothermal reaction product, wherein the molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution used is 3:0.45:0.55:1.
[0106] Comparative Example 9
[0107] The only difference from Example 3 is that:
[0108] Step 3: centrifuge the hydrothermal reaction product obtained in step 2, separate the solid and liquid, wash the solid product with anhydrous ethanol and deionized water, dry it, and mix the dry product with the carbon source obtained in step 1, wherein the amount of the carbon source added is 7.5% of the mass of the dry product to obtain a mixture.
[0109] Comparative Example 10
[0110] The only difference from Example 3 is that:
[0111] Step 3: centrifuge the hydrothermal reaction product obtained in step 2, separate the solid and liquid, wash the solid product with anhydrous ethanol and deionized water, dry it, mix the dry product with the carbon source obtained in step 1, and add the carbon source in an amount of 21% of the mass of the dry product to obtain a mixture.
[0112] Comparative Example 11
[0113] The only difference from Example 3 is that:
[0114] Step 4: ball mill the mixture obtained in step 3 at a ball milling speed of 300 r / min for 4 h to obtain a powder.
[0115] Comparative Example 12
[0116] The only difference from Example 3 is that:
[0117] Step 5: calcine the powder obtained in step 4 under inert gas protection at a calcination temperature of 500°C, a calcination time of 7h, a heating rate of 3°C / min, and naturally cool to room temperature to obtain a high-energy lithium manganese iron phosphate positive electrode material.
[0118] Comparative Example 13
[0119] The only difference from Example 3 is that:
[0120] Step 5: calcining the powder obtained in step 4 under inert gas protection at a calcination temperature of 550°C, a calcination time of 7h, a heating rate of 8°C / min, and naturally cooling to room temperature to obtain a high specific energy lithium manganese iron phosphate positive electrode material.
[0121] The high specific energy lithium iron manganese phosphate positive electrode materials prepared in Examples 3 to 13 and Comparative Examples 1 to 13 were subjected to application tests:
[0122] 1) Assembly of lithium iron manganese phosphate button battery: The lithium iron manganese phosphate positive electrode material obtained in the embodiment and the comparative example: SP (carbon black conductive agent): PVDF (polyvinylidene fluoride binder) was homogenized according to a mass ratio of 90:5:5, and then coated on a 20 μm thick aluminum foil and dried to prepare a positive electrode sheet; the obtained positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the PE-PP composite film was used as the battery separator, and 1 mol·L -1 LiPF6 / (DMC+DMC) was used as the electrolyte, in which the volume ratio of EC to DMC was 1:1, and assembled into a CR2032 button cell.
[0123] 2) 1C cycle performance test at 25°C: The lithium manganese iron phosphate button cells in the embodiments and comparative examples were tested using a blue electric tester. The prepared button cells were placed in a high temperature oven at 25°C for charge and discharge tests. The voltage range was 2.0V-4.35V, and 0.1C charge and discharge was activated for one cycle. Then, it was charged at a constant current and constant voltage of 0.5C, the cut-off current was 0.05C, and the constant current discharge was performed at a current of 1C. After 100 cycles, the relevant data of the first discharge capacity of 0.1C and 1C and the discharge capacity of the 100th cycle were obtained. The test results are shown in Table 1:
[0124]
[0125] It can be seen from the data in Table 1 that the present invention controls the ratio of lithium, manganese, iron and phosphorus in the lithium iron phosphate positive electrode material, the addition of carbon source and the amount of carbon source within the required range, as well as the control of parameters in the preparation process, so that the prepared lithium iron phosphate positive electrode material has electrochemical performance and cycle performance. The tap density of the lithium iron phosphate positive electrode material is higher than 0.97g / cm -3 At a discharge rate of 0.1C, the first discharge specific capacity can reach up to 165.5mAh / g, and at a discharge rate of 1C, the first discharge specific capacity can reach up to 155.6mAh / g, and it can still maintain excellent discharge specific capacity after 100 cycles.
[0126] Compared with Example 3, the lithium iron manganese phosphate material is not carbon-coated in Comparative Example 1, only carbon nanotubes are used as the carbon source in Comparative Example 2, and only xanthan gum is used as the carbon source in Comparative Example 3. It can be seen from the data in Table 1 that, compared with not using a carbon source or using a single organic or inorganic carbon source, the use of the composite carbon source prepared in the present invention can more comprehensively improve the electrochemical properties of the lithium iron manganese phosphate material, and significantly improve the conductivity and battery performance of the lithium iron manganese phosphate material by forming a more uniform coating layer and a better conductive network.
[0127] Compared with Examples 3-13, the parameters set in the process of preparing lithium iron manganese phosphate materials in Comparative Examples 4-13 are beyond the range set in the present invention, and the electrochemical properties of the obtained lithium iron manganese phosphate materials are lower than those of the materials prepared in Examples 3-13. It can be seen that the use, proportion and production process of raw materials in the process of preparing lithium iron manganese phosphate positive electrode materials will affect the electrochemical properties of lithium iron manganese phosphate positive electrode materials.
[0128] In summary, the present invention provides a method for preparing a high-energy lithium iron manganese phosphate positive electrode material, which not only improves the electrochemical properties of the lithium iron manganese phosphate material, so that the capacity of the lithium iron manganese phosphate material can be well utilized, but also ensures the cyclic stability of the material; and the preparation method is simple, economical, and suitable for continuous, large-scale industrial production.
[0129] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0130] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0131] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0132] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high specific energy lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1, adding carbon nanotubes into deionized water, ultrasonically dispersing, adding modified xanthan gum, ammonia water and hydrazine hydrate, stirring for 5-10 minutes, heating to 55-60°C, continuing stirring for 4-4.5 hours, filtering, washing, and drying to obtain a carbon source; Step 2, adding the lithium hydroxide solution to the phosphoric acid solution, stirring and dispersing, adjusting the pH value, adding the manganese sulfate solution and the ferrous sulfate solution, and then transferring to a hydrothermal reactor for a hydrothermal synthesis reaction to obtain a hydrothermal reaction product; Step 3, centrifuging the hydrothermal reaction product obtained in step 2, separating the solid from the liquid, washing the solid product with anhydrous ethanol and deionized water, drying, and mixing the dried product with the carbon source obtained in step 1 to obtain a mixture; Step 4, ball milling the mixture obtained in step 3 to obtain a powder; Step 5, calcining the powder obtained in step 4 under the protection of inert gas, and naturally cooling to room temperature to obtain a high specific energy lithium manganese iron phosphate positive electrode material; Wherein, the modified xanthan gum described in step 1 is prepared by the following steps: Add xanthan gum to sodium hydroxide solution, heat and stir to dissolve it, add 1,4-butanesulfonic acid lactone dropwise, stir and react at 70-75°C for 4-4.5 hours, cool to room temperature, adjust the pH value to 9-9.2, then add methanol until no more white precipitate is precipitated, let stand for 12-14 hours, filter and wash, and vacuum dry to constant weight to obtain modified xanthan gum.
2. The method for preparing a high specific energy lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of lithium, manganese, iron and phosphorus in the lithium hydroxide solution, manganese sulfate solution, ferrous sulfate solution and phosphoric acid solution is 3: (1-x): x: 1, wherein 0.1≤x≤0.
4.
3. The method for preparing a high specific energy lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step 1, the usage ratio of carbon nanotubes, deionized water, modified xanthan gum, ammonia water and hydrazine hydrate is 0.010-0.015 g: 20 mL: 0.32-0.36 g: 0.30 mL: 0.02 mL.
4. The method for preparing a high specific energy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The dosage ratio of xanthan gum, sodium hydroxide solution and 1,4-butanesulfonate is 5.0-5.5g:10mL:3.0-3.2mL.
5. The method for preparing a high specific energy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step 2, the pH value is adjusted to 9-11; in step 2, the hydrothermal synthesis reaction temperature is 180-220° C., and the reaction time is 12-22 hours.
6. The method for preparing a high specific energy lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The amount of carbon source added in step 3 is 10%-18% of the mass of the dry product.
7. The method for preparing a high specific energy lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step 4, the ball milling speed is 350-400 r / min, and the ball milling time is 3-4 h.
8. The method for preparing a high specific energy lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step 5, the calcination temperature is 550-600° C., the calcination time is 4-8 h, and the heating rate is 3-5° C. / min.
9. A high specific energy lithium manganese iron phosphate positive electrode material, characterized in that: The material is prepared by the method for preparing a high specific energy lithium manganese iron phosphate positive electrode material as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Hydrothermal synthesis method for lithium ferromanganese phosphate anode material of lithium ion battery
CN102249208A
Preparation method of lithium iron manganese phosphate serving as anode material of lithium ion battery
CN114665058A